Mechanochromic polymers with a multimodal chromic transition: mechanophore design and transduction mechanism. Issue 36 (31st August 2022) - Kim, Daewhan; Kwon, Min Sang; Lee, Chung Whan
Abstract : This review presents the recent progress in multi-chromic polymers embedded with mechanophores concentrating on transduction mechanisms and design concepts. Abstract : Mechanochromic polymers have been widely investigated in terms of their colour changes in response to external mechanical forces. This unique optical property can enable their use in a wide range of novel applications. Starting with their simple on–off mechanism, mechanochromic polymers have been advanced to exhibit multi-chromic transitions by several strategies, including the development of novel mechanophores and polymer linkages. This review aims to present the recent progress in the growing field of multi-chromic polymers embedded with mechanophores by concentrating on transduction mechanisms and design concepts. It was found that mechanophores can be carefully engineered to exhibit new transition modes using various concepts.